Effects of community-wide vaccination with PCV-7 on pneumococcal nasopharyngeal carriage in the Gambia: a cluster-randomized trial. - Anna Roca; Philip C Hill; John Townend; Uzo Egere; Martin Antonio; Abdoulie Bojang; Abiodun Akisanya; Teresa Litchfield; David E Nsekpong; Claire Oluwalana; Stephen R C Howie; Brian Greenwood; et al. (PLoS Medicine)
Background Introduction of pneumococcal conjugate vaccines (PCVs) of limited valency is justified in Africa by the high burden of pneumococcal disease. Long-term beneficial effects of PCVs may be countered by serotype replacement. We aimed to determine the impact of PCV-7 vaccination on pneumococcal carriage in rural Gambia. Methods and findings A cluster-randomized (by village) trial of the impact of PCV-7 on pneumococcal nasopharyngeal carriage was conducted in 21 Gambian villages between December 2003 to June 2008 (5,441 inhabitants in 2006). Analysis was complemented with data obtained before vaccination. Because efficacy of PCV-9 in young Gambian children had been shown, it was considered unethical not to give PCV-7 to young children in all of the study villages. PCV-7 was given to children below 30 mo of age and to those born during the trial in all study villages. Villages were randomized (older children and adults) to receive one dose of PCV-7 (11 vaccinated villages) or meningococcal serogroup C conjugate vaccine (10 control villages). Cross-sectional surveys (CSSs) to collect nasopharyngeal swabs were conducted before vaccination (2,094 samples in the baseline CSS), and 4-6, 12, and 22 mo after vaccination (1,168, 1,210, and 446 samples in CSS-1, -2, and -3, respectively). A time trend analysis showed a marked fall in the prevalence of vaccine-type pneumococcal carriage in all age groups following vaccination (from 23.7% and 26.8% in the baseline CSS to 7.1% and 8.5% in CSS-1, in vaccinated and control villages, respectively). The prevalence of vaccine-type pneumococcal carriage was lower in vaccinated than in control villages among older children (5 y to <15 y of age) and adults (≥15 y of age) at CSS-2 (odds ratio [OR] = 0.15 [95% CI 0.04-0.57] and OR = 0.32 [95% CI 0.10-0.98], respectively) and at CSS-3 (OR = 0.37 [95% CI 0.15-0.90] for older children, and 0% versus 7.6% for adults in vaccinated and control villages, respectively). Differences in the prevalence of non-vaccine-type pneumococcal carriage between vaccinated and control villages were small. Conclusions Vaccination of Gambian children reduced vaccine-type pneumococcal carriage across all age groups, indicating a "herd effect" in non-vaccinated older children and adults. No significant serotype replacement was detected. Please see later in the article for the Editors' Summary.